(untitled) (Research, Society and Development, 2021)
This study aimed to estimate the genetic divergence between matrices of Parkia pendula, native in the Amazon region of Mato Grosso, based on the biometry of seed fruits. For the biometric description of the fruits and seeds, the length, width, thickness and mass of the fruits, length, width, thickness and mass of the seeds were evaluated. The average length, width, thickness and fresh weight of the fruits were 149.53 mm, 22.60 mm, 5.97 mm and 7.13 g, respectively. The variation coefficient was found to be 12.5% for the width, reaching 30.86% for the thickness of the fruits. The variable of fresh weight of the seeds presented a frequency of 86%, concentrating four classes. The UPGMA grouping method, considering the cutoff point of 79% of distance, allowed the formation of five distinct groups. It was concluded that there was great genetic diversity for attributes related to the morphological characteristics of fruits and seeds.